Examining the contribution of taboos (Amazilo) towards eco-beneficial practices: Evidence from Ndebele linguistic wisdom - Busani Maseko; Bhekezakhe Ncube (Sustainable Environment)
Although environmental conservation has emerged as a prominent concern among researchers globally, much interest has been confined to the natural sciences. In this study, we deploy the ecolinguistics framework to examine the contribution of taboos towards an eco-beneficial ecosophy among the Ndebele people of Zimbabwe. Drawing on purposefully selected taboos from two anthologies of Ndebele oral literature, complemented by authors’ intuitions, our findings reveal that the Ndebele language is imbued with ecocentric wisdom that is encoded in taboos. These environmental taboos warn against the unsustainable exploitation of fauna and flora species as well as the contamination or desecration of water sources. Additionally, needless destruction and degradation of land are discouraged by some taboos. These findings suggest that the Ndebele people’s harmonious relationship and co-existence with their natural environment derive from age-old wisdom that is embedded in their linguistic system as part of their environmental policy, laws and ethics. Contrary to enduring colonial ideologies that have sought to portray indigenous African languages as incapable of addressing modern problems associated with climate change and other anthropogenic activities, we show that languages such as Ndebele evince the positive environmental stewardship and disposition that have been part of African communities since time immemorial.